STRATEGI PENGEMBANGAN USAHATANI DURIAN MONTONG DI DESA SUKARAJA KECAMATAN WAY TENONG KABUPATEN LAMPUNG BARAT (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
This search was conducted in the village sukaraja subdistrict way tenong west lampung district, has been implemented in November 2017, this study aims to examine the strategy development of durian montong farming in the village sukaraja, this research is done in the village sukaraja using survey research methods and using the method of withdrawal sample with census method with sample determination of 36 sample that all farmers of montong durian taken all, trader 3, consumer 5, and agricultural extension 3. The result showed that the value of IFAS 2,19 which proves the internal position in the average which proves the internal position in the average and the total value of EFAS is 2,60 which means agribusiness durian montong has a very prospective opportunity and able to minimize the threat. With the conclusion should be farmers to maintain durian montong money farming in the farmers because demand is growing, and can open business opportunity and is recommended to the farmers of durian montong pay more attention to the cleanliness of the land for durian plants are not susceptible to fungal diseases on the roots and is expected to support and capital assistance from government in durian montong farming in order to expand the land in the effort by farmers-farmers